Agronomic performance of new peanut lines in the Alta Paulista region at the time of planting opening - Zammataro, Diego Dias (2021)
This study aimed to evaluate the agronomic performance of twelve peanut genotypes, in the Alta Paulista region, municipality of Parapuã, in the state of São Paulo. The experiment was carried out in the experimental area of "‹"‹Cooperativa Casul, located in the western region of the state, in the municipality of Parapuã-SP, in the agricultural year 2020/21. The experimental design used was in randomized blocks, with four replications. The treatments consisted of twelve peanut genotypes, ten strains (1253 OL, 2010 OL, 1876 OL, 2133 OL, 2110 OL, 2131 OL, 2101 OL, 2056 OL, 2136 OL and 2250 OL) and a cultivar (BRS 423 OL) developed by Embrapa's PMA, and an Argentine cultivar by El Carmen (Granoleico). The plots consisted of two lines three meters long, with a spacing of 0.90 m and a useful area for evaluation of 5.4 m2 per plot. Mass of 100 grains and pod yield were evaluated. Based on the present field study, it is concluded that the genotypes showed a significant difference both in the mass of 100 grains, demonstrating granulometric amplitude to meet the different market niches, and in the productivity of pods with superiority observed in the 2010 OL strains, 1876 OL and 2133 OL, with yields greater than 6,800 kg.ha-1.